Transepithelial Photorefractive Keratectomy with Crosslinking for Keratoconus - Mukherjee, Achyut N (Bentham Open, 2013)
PURPOSE: To analyse visual, refractive and topographic outcomes of combining transepithelial photorefractive keratectomy (tPRK) with simultaneous corneal crosslinking for the visual rehabilitation of contact lens intolerant keratoconus patients. METHODS: Patients with topographically significant keratoconus, limited corrected vision and intolerant of contact lenses were prospectively recruited, subject to ethical approval and consent. All patients underwent single step aspheric tPRK and sequential crosslinking. Preoperative vision, refraction, corneal topography and wavefront were assessed, with postoperative assessment at 1, 3, 6, and 12 months. RESULTS: 22 eyes of 14 patients were included in the pilot study. Mean age was 32 years (SD 6.8, range 24 to 43). Mean preoperative unaided vision was 1.39 LogMAR (SD 0.5) best corrected 0.31 LogMAR (SD 0.2). Mean preoperative spherical equivalent was -2.74 Diopters (D) (SD 4.1 range -12.25 to +7.75), and mean cylinder -2.9 D (SD 1.2, range 0 to -5.5). Mean central corneal thickness was 461um (SD 29, range 411 to 516). Vision improved postoperatively; unaided 0.32 LogMAR (SD 0.4), best corrected 0.11 (SD 0.13) (P=<0.005). Mean postoperative cylinder was -1.4D (SD1.2), significantly reduced (p<0.005). Maximum keratometry (Kmax) was stable throughout postoperative follow up. (p<0.05). CONCLUSIONS: Non topographic transepithelial PRK with simultaneous crosslinking improves vision, and may offer an alternative to keratoplasty in contact lens intolerant keratoconus. Further comparative studies to topographic PRK techniques are indicated.